PATTERNS OF FLUID FLOW IN THE CONTACT AUREOLE OF THE LATE MIOCENE MONTE CAPANNE PLUTON (ELBA ISLAND, ITALY): THE ROLE OF STRUCTURES AND RHEOLOGY - Rossetti F.; Tecce F.; Billi A.; Brilli M. (My University, 2007)
Fluid–rock interaction was investigated in the inner aureole of the Late Miocene Monte Capanne pluton on Elba Island (Tuscany, central Italy) by integrating structural, petrological, fluid inclusion, and stable isotope analyses. In the north-western sector of the aureole (Procchio–Spartaia area), calc–silicates alternate with nearly pure carbonate layers at the metre scale. Close to the pluton, the prograde metamorphic sequence includes calc–silicates that transition within a few metres to overlying nearly pure calcite marbles. The calc–silicates are extensively metasomatised to form massive wollastonite-grossular-bearing exoskarn. The mineralogical assemblage found in the marbles and the unshifted carbon and oxygen isotopic ratios in calcite attest that the fluid phase was internally buffered. On the other hand, the calc–silicates constituted channels for infiltration of disequilibrium fluids of magmatic origin. Fluid infiltration was enhanced by hydrofracturing and structurally-controlled by existing planar anisotropies in calc–silicates (layering and lithological boundaries). At the metamorphic peak (~600°C and 1.5–2 kbar), the marble–calc–silicate interface acted as a barrier to fluids exsolved from the crystallising intrusions, separating two different flow patterns in the inner aureole: a high fluid–flux region on its higher grade side (Wol-zone) and a low fluid–flux region on the lower-grade side (Cpx zone). Results of this study: (1) documented that fluid pathways in the aureole rocks at the top of the pluton were largely horizontal, controlled by the lithological layering and the pluton–host rock contact; and (2) elucidated the primary control exerted by the structural and rheological properties of the host rocks on the geometry of fluid flow during pluton emplacement.
Keywords: FLUID INCLUSION; HYDROFRACTURING; WOLLASTONITE; SILICATE ROCK; GEOTHERMAL FIELD; Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен